Sala virtual de recursos multifuncionais para potencializar o atendimento educacional especializado - Roveder, Ângela Balbina Picada (2015)
This study linked to the line of research "Development of network educational technology", from the Professional Master course on Network Educational Technology, aims to contribute to the provision of Specialized Educational Service (SES). To do so, it was sought to develop a Digital Educational Material (DEM) to enhance SES; specifically the objectives were: 1) expand the SES, implementing a DEM in order to be used presentially and at a distance; 2) adapt the pedagogical model DEM, making it accessible to the target audience of the Special Education Student (SPES) and 3) validate the possibilities of motivation, autonomy and learning of DEM with SPES, under the assessment of SES teachers. On the basis of theories, it can include four axes: first, contemplating the special education; the second, with studies of digital educational materials, Learning objects; the third on Teaching Design (TD) in the construction of DEM and the fourth axis referring to the accessibility of digital educational materials. By applying a qualitative research, the focus was on teachers who work in Multifunctional Resource Rooms, performing the SES of state public schools in the city of Santa Maria, RS state. Data collected went through content analysis (Bardin, 2011), using three categories: motivation for the use of DEM, the autonomy in the use of DEM and potential for learning. The results of the analyzed categories allow evidence that the motivation to use DEM is present due to the context of illustrations, content and accessibility; as the autonomy, the results indicate that the non-linear path and affordable navigation possibilities are important characteristics for the development of a DEM, and finally, the potential for learning is present from the developed educational activities in accordance with the practices the SES and the possibilities of using DEM presentially and at distance. Thus, the study achieved its goals, understanding that the virtual room of multifunction resources gives SES greater potential.